2005
DOI: 10.21236/ada445094
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of the Problem of the Computational Time Reversal in the Quadrant

Abstract: The problem of the computational time reversal is posed as the inverse problem of the determination of an unknown initial condition with a finite support in a hyperboilc equation, given the Cauchy data at the lateral surface. A stability estimate for this ill-posed problem implies refocusing of the time reversed wave field. Two such two-dimensional inverse problems are solved numerically in the case when the domain is a quadrant and the Cauchy data are given at finite parts of coordinate axis. The previously o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…A comprehensive numerical study of the proposed numerical method was conducted. This study has demonstrated robustness of our technique with respect up to 50% random noise in the data, similarly with previous publications [4], [12], [15]. This study has also demonstrated that this method is capable to image sharp peaks, which is important for the application to thermoacoustic tomography, for example.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A comprehensive numerical study of the proposed numerical method was conducted. This study has demonstrated robustness of our technique with respect up to 50% random noise in the data, similarly with previous publications [4], [12], [15]. This study has also demonstrated that this method is capable to image sharp peaks, which is important for the application to thermoacoustic tomography, for example.…”
Section: Discussionsupporting
confidence: 88%
“…The method of multipliers was recently extended to the case of non-zero lower order terms in Theorem 3.5 of the book [6]. The above problems were previously solved numerically in [4], [7], [12] and [15]. The work [7] was the first one, where the problem of thermoacoustic tomography was formulated and solved numerically as Inverse Problem 1, i.e., as the hyperbolic Cauchy problem with the lateral data.…”
Section: Suppose Thatmentioning
confidence: 99%
See 3 more Smart Citations